Kandungan Total Fenol dan Aktivitas Antibakteri Kelopak Buah Rosela Merah dan Ungu Sebagai Kandidat Feed Additive Alami Pada Broiler - Putri, Dwi Desmiyeni; Nurmagustina, Dwi Eva (Politeknik Negeri Lampung., 2014)
Broiler farming always use feed additives commercial to improve productivity of broiler, but feed additives commercial have negative effect for consument. Feed additive should have ability as an antibacterial. To minimize using commercial feed additive we have to find alternatives to optimize the use of roselle calyces. This experiment was conducted to knowing phenol content and antibacterial activity of red roselle (Hibiscus sabdariffa) calyces and purple roselle (Hibiscus sabdariffa) calyces and to determine the type of roselle calyces which have potential as feed additive candidate on broiler. The phenol content was conducted using visible spectrophotometry method with Folin Ciocalteau reagen, and the antibacterial activity using agar well method for measuring clearing zone againt Staphylocccus aureus and Escherichia coli. The results showed that difference in solvent temperature (300C, 600C and 900C) of red and purple roselle calyces didn?t affect the phenol content, but the extract 10% of purple roselle calyces containing phenol content higher than the extract of red roselle calyces. The difference of solvent temperature didn?t affect the antibacterial activity, but extracts 10% of purple roselle calyces have antibacterial activity higher than red roselle calyces. Purple roselle calyces more potencial as feed additive. Keywords : Roselle (Hibiscus sabdariffa) calyces, phenol content, antibacterial activity